Prevalence rate of cornea diseases according materials of outpatient facilities in Baku city - P. M. Maharramov (Российский офтальмологический журнал, 2021)
Purpose: to assess the prevalence of corneal diseases using the data on the incidence of visits to outpatient facilities in the city of Baku. Material and methods. The data, presented by outpatient facilities for the year 2017, were statistically analyzed. Results. It was revealed that, for every 100 000 people, there were 266.1±3.4 cases of corneal diseases of which 97.9 ± 2.1 were infectious and 166.9 ± 2.7 were noninfectious diseases. Corneal neoplasms were detected in 1.3 ± 0.2 cases. The ratio of non-infectious and infectious diseases ofthe cornea was ca. 1.7. The lowest prevalence rate of both infectious and non-infectious diseases of the cornea was detected in children aged 0 to 9 years. In older age groups, the change of prevalence of corneal diseases was found to be chaotic. The trends of age-related prevalenceof infectious vs. non-infectious diseases of the cornea were basically similar; the highest rate was detected among patients aged 60–69. Conclusion.According to the appealability data, the prevalence rate of corneal diseases is rather high and age-dependent with a prevailing share of non-infectious corneal pathologies. In male population, this rate is notably lower than in female population.